الأبعاد التشكيلية والتعبيرية لفن الديكور التلفزيوني كمدخل لإثراء العملية التدريسية لطلاب قسم التصميم الداخلي - الشيباني، ليلى محمد سعيد (جامعة حلوان - كلية التربية الفنية, 2016)
لم تحظ مادة الديكور التلفزيوني بالاهتمام المناسب والكاف من الدراسة والبحث، رغم ما تحتويه هذه الفنون من طابع فني مميز جميل، ومن قيم فنية وجمالية وإمكانية استثمارها والاستفادة منه كمدخل تجريبي ليثري العملية التعليمية لطلاب المستوى الرابع بقسم التصميم الداخلي بكلية الفنون الجميلة باليمن - حتى تزيد طاقات التعبير الفني عند الطلاب لاكتساب عناصر الإبداع والابتكار في أعمال الطلاب الفنية. ومن ثم، رأت الباحثة أهمية التطرق إلى العناصر التشكيلية والتعبيرية والقيم الجمالية للديكور التلفزيوني حتى يسهم بدوره تنمية الرؤية الفنية للطلاب، مما يساعد على إنتاج أعمال فنية تتسم بالإبداع والابتكار. وعليه تطرق البحث بالإطار النظري بأهم القيم التشكيلية والتعبيرية لفن الديكور التلفزيوني لإثراء العملية التدريسية لطلاب قسم التصميم الداخلي بكلية الفنون الجميلة باليمن.
The television décor course was not fortune to have the appropriate And sufficient attention of study and research , in spite of what These arts contains of a pretty and distinguish artistic character , as Well as artistic aestheticism principles and the possibility to Utilized and benefit of it as an experimental entrance to enrich the Students educational process at the fourth level of the interior Design section at the Yemeni faculty of fine art – in order to Increase the students capacity of the artistic expression to acquire The innovation and creativity elements in the students artistic Works. Consequently the researcher realized the importance to Turn into the aesthetical principles, expressive, formational Elements of the television decoration so it can participate in its role To develop the students artistic vision , which will help in Producing an artistic works characterized by innovation and Creativity, accordingly the research turned into the theoretical Frame to the most important formational and aesthetical principles Of the television decoration art to enrich the educational process of The students at the Yemeni faculty of fine art – interior design section
Keywords: التعليم الجامعي -- التصميم الداخلي -- الديكور التلفزيوني -- القيم الجمالية -- القيم التشكيلية -- كلية الفنون الجميلة -- اليمن